Knowledge and Preventive Practice of Pulmonary Tuberculosis Among Tuberculosis Patients in Chitwan District - Kalakheti, Kamal; Poudyal, Jiwan Kumar; Upadhyay, Hari Prasad; Adhikari, Alina; Adhikari, Sudip; Sedain, Prativa (Journal of National Heart and Lung Society Nepal, 2022)
Background: Tuberculosis (TB) is one of the world's most serious infectious diseases caused by Mycobacterium tuberculosis. Tuberculosis typically attacks the lungs, but can also affect other parts of the body.Methods: An analytical cross-sectional study was conducted patients who were suffering from tuberculosis and taking Anti-TB medicine from different DOTS center of Chitwan District during the 22nd August to 3rd September 2021. Data was analyzed using descriptive and inferential statistical tools in SPSS-20. p-value